Experimental Research on Chip Morphology of Ti-5553 Cutting under High-Pressure Cooling. Issue 1 (13th October 2022) - Wang, Liang; Li, Rongyi; Liu, Erliang; Zhang, Hongyan
Abstract: Because Ti-5553 is a kind of difficult-to-machining material, this study uses high-pressure cooling to assist machining and compares it with dry cutting to observe the change of chip morphology in the cutting process. Firstly, a comparative analysis of the chip's macroscopic morphology is carried out, and then the microscopic morphology difference of the chip and its influence on the macroscopic morphology are explored. Furthermore, it provides an intuitive basis for evaluating the cutting performance of Ti-5553 under high-pressure cooling. Experimental research shows that the chips generated under high-pressure cooling are more conducive to chip breaking.